2004
DOI: 10.1002/chin.200412160
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Potential Selective COX‐2 Enzyme Inhibitors Derived from Ethyl Ester of 2‐Isothiocyanato‐5‐phenyl‐3‐thiophenecarboxylic Acid.

Abstract: Derivatives containing the thieno [2,3-d]pyrimidin-4-one system, potential selective COX-2 inhibitors, were prepared starting from ethyl ester of 2-isothiocyanato-5-phenyl-3-thiophenecarboxylic acid (2); their structural elucidation is also reported.J. Heterocyclic Chem., 40, 869 (2003).Derivatives containing the thienopyrimidine systems are reported to possess several important pharmacological properties [1]; in particular some derivatives of the 6-showed interesting anti-inflammatory and analgesic activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The synthetic route to prepare the new isomers thioaryl and thiocycloesyl derivatives of the heterocyclic system 6-phenylthieno [3,2] pyrimidinone by up-to-date method is reported in Figure 1. The several steps to synthetize the compounds are shown in Supplementary Data S1.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…The synthetic route to prepare the new isomers thioaryl and thiocycloesyl derivatives of the heterocyclic system 6-phenylthieno [3,2] pyrimidinone by up-to-date method is reported in Figure 1. The several steps to synthetize the compounds are shown in Supplementary Data S1.…”
Section: Chemistrymentioning
confidence: 99%
“…In previous papers, we demonstrated that thieno[2,3‐d]pyrimidinone methanesulfonamides thio‐derivatives show an interesting selective COX‐2 anti‐inflammatory activity without toxic effects on cells. These derivatives were designed by bioisosterically replacing the carbon‐carbon double bond as in the coxibs stilbene scaffold through a sulphur atom and molecular hybridization with the lead L‐745 337 and the thienopyrimidin‐4‐one moiety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation